1999
DOI: 10.1152/jn.1999.82.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Alphaxalone Activates a Cl Conductance Independent of GABAA Receptors in Cultured Embryonic Human Dorsal Root Ganglion Neurons

Abstract: Whole cell and cell-attached patch-clamp techniques characterized the neurosteroid anesthetic alphaxalone's (5alpha-pregnane-3alpha-ol-11,20-dione) effects on GABAA receptors and on Cl- currents in cultured embryonic (5- to 8-wk old) human dorsal root ganglion neurons. Alphaxalone applied by pressure pulses from closely positioned micropipettes failed to potentiate the inward Cl- currents produced by application of GABA. In the absence of GABA, alphaxalone (0.1-5.0 microM) directly evoked inward currents in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…This suggests that, at high concentrations , alphaxalone directly activates the GABA A receptor/chloride channel complex in the absence of GABA, increasing the chloride conductance. Similar ndings were reported for cultured human embryonic dorsal root ganglion neurons (VALEYEV et al, 1999a;1999b). Barker and colleagues (BARKER et al, 1987) have shown in cultured rat spinal neurons that alphaxalone increases the chloride conductance by increasing the mean open time of the GABA activated channels, and directly activates the chloride conductance by stimulating long duration channel openings.…”
Section: Effects Of Saffan R°o N Gamma-aminobutyric Acid (Gaba) Recepsupporting
confidence: 70%
“…This suggests that, at high concentrations , alphaxalone directly activates the GABA A receptor/chloride channel complex in the absence of GABA, increasing the chloride conductance. Similar ndings were reported for cultured human embryonic dorsal root ganglion neurons (VALEYEV et al, 1999a;1999b). Barker and colleagues (BARKER et al, 1987) have shown in cultured rat spinal neurons that alphaxalone increases the chloride conductance by increasing the mean open time of the GABA activated channels, and directly activates the chloride conductance by stimulating long duration channel openings.…”
Section: Effects Of Saffan R°o N Gamma-aminobutyric Acid (Gaba) Recepsupporting
confidence: 70%
“…DRG, located along the spinal nerves, house the cell bodies of sensory neurons whose dendrites are located in the skin, muscles, tendons, joints and internal organs. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Studies of dissociated human dorsal root ganglion (hDRG) neurons have described changes in electrophysiology and ion channel function due to changing culture conditions, 23 exposure to viral proteins, 25 drugs, and chemicals. 5 Lack of access to primary human sensory neurons has hindered the understanding of the physiology of pain in humans; 6 most investigations have been performed on neurons retrieved from ganglionectomized chronic pain patients or fetal and autopsy tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] In a few cases, viable human tissues have been dissociated into single neurons and utilized to characterize receptor function using traditional electrophysiological methods, such as patch clamping, to monitor alterations in the electrophysiological response. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Studies of dissociated human dorsal root ganglion (hDRG) neurons have described changes in electrophysiology and ion channel function due to changing culture conditions, 23 exposure to viral proteins, 25 drugs, and chemicals. 24,[26][27][28][29] While these techniques are very informative, they are restricted to individually interrogating single cells.…”
Section: Introductionmentioning
confidence: 99%